The Linguistics of Imaginary Narrative Spaces in Daphne du Maurier’s Rebecca - John Newman (East European Journal of Psycholinguistics, 2018)
Daphne du Maurier’s 1938 novel Rebecca provides rich opportunities for the study of imaginary narrative spaces and the language associated with such spaces. The present study explores the linguistics of the imaginary narrative spaces in Rebecca, drawing upon three lines of linguistic research consistent with a Cognitive Linguistic approach: (i) an interest in understanding and appreciating ordinary readers’ actual responses (rather than merely relying upon “expert” readers’ responses), (ii) the construction of worlds or “spaces”, and (iii) the application of ideas from Cognitive Grammar. The study reveals a surprisingly intricate interplay of linguistic devices used in the construction of imaginary narrative spaces and the maintenance of such spaces in extended discourse.ReferencesArmitt, L. (2000). Contemporary women’s fiction and the fantastic. New York: St. Martin’s Press.Beauman, S. (2003). Afterword. In Daphne du Maurier’s Rebecca (pp. 429-441). London: Virago Press.Biber, D., Johansson, S., Leech, G., Conrad, S., & Finnegan, E. (Eds.) (1999). Longman grammar of spoken and written English. Harlow, UK: Pearson Education Limited.Birch, D. (2007). Addict of fantasy. The Times Literary Supplement, 5447-5448, 17-18.Dancygier, B. (2012). The language of stories: A cognitive approach. Cambridge: Cambridge University Press.Dancygier, B. (2017a). Introduction. In B. Dancygier (Ed.), The Cambridge handbook of cognitive linguistics (pp. 1-10). Cambridge: Cambridge University Press.Dancygier, B. (2017b). Cognitive Linguistics and the study of textual meaning. In B. Dancygier (Ed.) The Cambridge handbook of cognitive linguistics (pp. 607-622). Cambridge: Cambridge University Press.Du Maurier, D. (2012). Rebecca. London: Virago Press.Emmott, C. (1997). Narrative comprehension: A discourse perspective. Oxford: Oxford University Press.Evans, V., & Green, M. (2006). Cognitive linguistics: An introduction. Edinburgh: Edinburgh University Press.Fauconnier, G. (1985). Mental spaces: Aspects of meaning construction in natural language. Cambridge: Cambridge University Press.Forster, M. (1993). Daphne Du Maurier. London: Chatto & Windus.Gavins, J. (2007). Text world theory: An introduction. Edinburgh: Edinburgh University Press.Hadiyanto, H. (2010). The Freudian psychological phenomena and complexity in Daphne Du Maurier’s “Rebecca” (A psychological study of literature). LITE: Jurnal Bahasa, Sastra, Dan Budaya 6(1), 14-25. Available at: https://publikasi.dinus.ac.id/index.php/lite/article/ view/1348/1014.Harrison, C., Nuttall, L., Stockwell, P., & Yuan, W. (Eds.) (2014). Cognitive grammar in literature. Amsterdam & New York: John Benjamins.Harrison, C., & Stockwell, P. (2014). Cognitive poetics. In J. Littlemore and J. R. Taylor (Eds.), The Bloomsbury companion to cognitive linguistics (pp. 218-233). London: Bloomsbury.Horner, A., & Zlosnik, S. (1998). Writing, identity, and the Gothic imagination. London: Macmillian.Huddleston, R. (2002). The verb. In R. Huddleston & G. K. Pullum (Eds.), The Cambridge grammar of the English language (pp. 71-212). Cambridge: Cambridge University Press.Kelly, R. (1987). Daphne du Maurier. Boston: Twayne Publishers.Lakoff, G., & Turner, M. (1989). More than cool reason: A field guide to poetic metaphor. Chicago & London: The University of Chicago Press.Langacker, R. W. (1991). Foundations of cognitive grammar. Vol. II: Descriptive application. Stanford, CA: Stanford University Press.Leech, G. N. (1969). A linguistic guide to English poetry. London: Longman Group Limited.Margawati, P. (2010). A Freudian psychological issue of women characters in Daphne Du Maurier’s novel Rebecca. LANGUAGE CIRCLE: Journal of Language and Literature IV(2), 121-126. Available at: https://journal.unnes.ac.id/nju/index.php/LC/article/viewFile/900/839Naszkowska, K. (2012). Living mirror: The representation of doubling identities in the British and Polish women’s literature (1846–1938). Doctoral dissertation, The University of Edinburgh.Palmer, F. R. (1974). The English verb. London: Longman Group Limited.Stockwell, P. (2002). Cognitive poetics: An introduction. London & New York: Routledge.Turner, M. (1996). The literary mind. New York & Oxford: Oxford University Press.Turner, M. (2015). Blending in language and communication. In E. Dąbrowska & D. Divjak (Eds.), Handbook of cognitive linguistics (pp. 211-232). Berlin & Boston: de Gruyter Mouton.Werth, P. (1999). Text worlds: Representing conceptual space in discourse (M. Short, Ed.). Harlow, UK: Longman.Wilde, O. (1996). The picture of Dorian Gray. In The complete Oscar Wilde: The complete stories, plays and poems of Oscar Wilde (pp. 11-161). New York: Quality Paperback Book Club.Winifrith, T. J. (1979). Daphne du Maurier. In J. Vinson (Ed.), Novelists and prose writers (Great writers of the English language) (pp. 354-357). New York: St. Martin’s Press.